Pré-tratamento de sementes de soja com o metil-jasmonato: indução da liberação de etileno durante simulação de estresse biótico e abiótico - Coy-Rodríguez, Vivian Andrea (2021)
Jasmonates are compounds that induce a direct constitutive defense against some stresses, both biotic and abiotic, and are used as elicitors in soybean to induce a defense against stressful biotic or abiotic conditions. However, its role in inducing the production of volatiles, specifically ethylene, during the germination process is poorly studied. In view of the above, the objectives of the present work were to evaluate the release of ethylene in soybean seeds (Glycine max (L.) Merr.) during the different phases of water absorption in the germination process, from seeds treated with different concentrations of MeJA ( Methyl-jasmonate), the relationship of ethylene release with the enzymes of the antioxidant system, superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and levels of hydrogen peroxide (H2O2), and malondialdehyde (MDA), in V1 vegetative stage soybean seedlings from seeds treated with MeJA. The growth of soybean seedlings treated or not with MeJA and submitted to water deficit condition and herviboria simulation was also evaluated. MeJA induced ethylene release in seeds during the different phases of water absorption, being the concentration of 12.5 μM of MeJA the one that presented the best results for germination speed index (IVG) and T50. Soybean seedlings from seeds treated with MeJA under herbivory simulation showed a significant difference in the content of ethylene released, compared to water deficit. Likewise, MeJA promoted higher levels of H2O2 and MDA for seedlings submitted to water deficit condition, but did not promote the activity of SOD, CAT and APX antioxidant enzymes under stressful conditions. Finally, in the growth variables, the water deficit condition caused less growth of stem and root, as well as root dry mass and number of leaves. With these results, it is concluded that MeJA induces the release of ethylene during the different phases of water absorption of the germination process and in soybean seedlings from seeds treated with MeJA under herviboria simulation, in addition to promoting higher levels of H2O2 and MDA for seedlings submitted to water deficit condition. This work provides a reference for research in the area of systemic resistance induction, as well as for analyzing the importance of the hormones MeJA and ethylene in the defense of plants against herviboria.